Design of LPG transport aids to prevent musculoskeletal risks - Dewantari, Nustin Merdiana; Fachrur, Aditya Rahadian; Mariawati, Ade Sri; Akbari, Rizky; Ferdiansyah, Muhammad; Annisa, Findi Choerun (Universitas Sultan Ageng Tirtayasa, 2023)
The Central Statistics Agency of Indonesia (BPS) has recorded an increase in the use of liquefied petroleum gas (LPG) by the public over the last seven years. This increase is due to the government changing its policy from using fuel oil to LPG. LPG is essential for the community as a kitchen fuel to meet their needs and for resale. Distributing LPG gas is crucial to meeting the community's needs. However, one of the distribution processes involves manual loading and unloading, which can cause musculoskeletal complaints. Therefore, tools that can facilitate work are necessary. This study aims to reduce the risk of musculoskeletal disorders by examining the working posture of transporting LPG gas at a LPG distributor in Indonesia. The study proposes a tool design to solve the problem of high work posture. The results of data processing and analysis show that the design of assistive devices can reduce the risk of work posture.